Factores determinantes en la sepsis de pacientes post quirúrgicos en el área de hospitalización San Vicente del Hospital General Martín Icaza Babahoyo, diciembre 2022 - mayo 2023. - Muñoz Briones, Ambar Dayanna (2023)
Post-surgical sepsis is a global health problem, with the greatest impact in low- and middle-income countries. This occurs when a microorganism invades tissues or organs, compromising the host's immune system, causing it to react to an infection, given that if If not treated in time, it can cause disability or complications, causing hemorrhage, multiple organ failure, septic shock, tissue damage, and death of the patient; they can also be acquired in the community or in medical care due to various determining factors. Some studies mention that 11 million people die from sepsis each year, including pregnant women and children. Therefore, the type of study was descriptive, observational, non-experimental and cross-sectional, due to the fact that a documentary review of the clinical histories of patients who presented sepsis in the hospitalization area of San Vicente surgery of the Martín Icaza General Hospital was carried out. , with the objective of identifying the determining factors, estimating a total of 389 patients, among them 10 presented sepsis, finding the age groups with the highest prevalence between 20 to 39 years in 46%, 45% with obesity showing a lifestyle inadequate, 22% with arterial hypertension and diabetes mellitus, 19% submitted to appendectomy, 15% herniorrhaphy and 12% exploratory laparotomy, with a time of onset of infection between 5 to 7 days, presenting clinical manifestations in a 3%, and 51% with prophylactic treatment with ceftriaxone, metronidazole, piperacillin and tazobactam.